Esterification of citric acid with locust bean gum - Hadinugroho, Wuryanto (Heliyon, 2019)
Esterification of citric acid (CA) with locust bean gum (LBG) was prepared by hydrochloric acid (HCl) as a catalyst and UV irradiation (254 nm) as esterification energy. This study aims to determine the best conditions of esterification. Other than that, it is to know the effect of amount HCl and UV irradiation time for the esterification process of CA with LBG. The amounts of HCl are 0.18 and 0.30 M, while the variations of UV irradiation time are 75 and 100 minutes. Polyester (CA-LBG) were characterized by Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance (NMR), scanning electron microscopy (SEM), differential scanning calorimetry (DSC), X-ray diffractometer (XRD), esterification degree, and viscosity. Parameters for determining the best conditions for esterification are esterification degree and viscosity. The best conditions of esterification were obtained by using 0.30 M mL HCl and 100 minutes of UV irradiation time resulted in CA-LBG having a value of esterification degree 9.69 % and viscosity 7.46 cPs. HCl accelerates protonation on the O atoms and the formation of positive C atoms of carbonyl groups of citric acid. The time of UV irradiation gives the longer energy for the bond formation between the positive C atoms of the carbonyl group and the O atoms of the hydroxyl group at C-6 atoms of mannose and galactose.